A reliable, simple and cost-efficient TLC-HPLC method for simultaneously determining florfenicol and florfenicol amine in porcine urine: application to residue surveillance. Issue 8 (3rd August 2019) - Qian, Mingrong; Zhou, Danna; Wang, Qianyong; Gao, Jindong; Li, Dong; Li, Yachao; Yang, Bo
ABSTRACT: Violative residues of florfenicol (FF) in porcine edible tissues pose a potential risk for human health. In this study, urine was selected as target matrix for routine residue monitoring of FF in pig, and a thin layer chromatography (TLC)-high-performance liquid chromatography (HPLC) method was developed for simultaneously determining FF and florfenicol amine (FFA) in porcine urine. The urine samples were extracted with ethyl acetate under alkaline environment. The extracts were enriched through evaporation, purified by TLC and analysed by HPLC at 225 nm. A Waters Symmetry C18 column was used for the separation of the two analytes. The mobile phase was acetonitrile-phosphate buffer mixtures (33.3: 66.7, v/v), and was pumped at 0.6 mL/min. The TLC-HPLC method was well validated and successfully applied to residue depletion study. Good analytical specificity was confirmed by the lack of interfering peaks at the retention times of FF and FFA. The standard curves showed good linearity (FF: y = 143064x – 1045.3, r = 0.9999; FFA: y = 275826x + 1888.8, r = 0.9999) over the range of 0.0625–8 μg/mL. The precision ranged from 0.83% to 11.66% and 2.19% to 8.75% for intraday and interday determination, respectively. The corresponding accuracy ranged from −13.38% to 10.78% and −12.15% to 7.14%, respectively. The limits of quantification (LOQs) for FF and FFA were 0.125 μg/mL. The residue depletion study showed that the concentrations of FF and FFA in urine were higher than those in edible tissues at three time points. This method was reliable, simple and cost efficient, and could be used to monitor FF residues in porcine edible tissue without slaughtering animals. TLC showed excellent purification efficiency and is expected to solve matrix interferences in veterinary drug residue analysis. Graphical abstract: